Peran Teknologi Informasi dan Komunikasi: Efektifitas dan Potensi Kinerja Kelompok - Luthfi Fauziyyah Nur’aiini; Bambang Samsul Arifin (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2021)
In general, performance in a group is carried out by face-to-face meetings, but for now, face-to-face meetings are not only means of communication by workgroups or organizations. In the last 20 years, information and communication technology (ICT) has shown a new communication platform, especially in working groups. So that emerging research that discusses workgroups that focus on new ways to communicate in groups. However, there are no studies to date that express communication via computers in groups over time. The researcher is interested in discussing it with quantitative research methods; data are taken from 44 participants, 22 groups working in face-to-face conditions, and 22 groups working in Zoom Meeting conditions. Participants are 11th-grade students of Madrasah Aliyah Banjaran who are enrolled in extra-curricular entrepreneurship. The mean age was 17 years old, 32 students were male (18%), and 144 were female (82%). The composition of each group has the same proportion. The results showed that virtual communication could improve group performance, and it is necessary to develop group potential in virtual teams.